2022
DOI: 10.1186/s12889-021-12413-0
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer mortality among young women in Latin America and the Caribbean: trend analysis from 1997 to 2030

Abstract: Background Cervical cancer continues to show a high burden among young women worldwide, particularly in low- and middle-income countries. Limited data is available describing cervical cancer mortality among young women in Latin America and the Caribbean (LAC). The purpose of this study was to examine the mortality trends of cervical cancer among young women in LAC and predict mortality rates to 2030. Methods Deaths from cervical cancer were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
(49 reference statements)
0
18
0
1
Order By: Relevance
“…The present results showed that the status quo of timely health seeking is not optimistic in this population; diagnosis delay and disease progression caused by patient delay might be important reasons for the poor prognosis in this population. 3 , 8 The overall trend demonstrated a decline in cervical cancer mortality, while cervical cancer deaths tended to occur in younger age-groups 2 , 36 (up to 5.5% annually). 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results showed that the status quo of timely health seeking is not optimistic in this population; diagnosis delay and disease progression caused by patient delay might be important reasons for the poor prognosis in this population. 3 , 8 The overall trend demonstrated a decline in cervical cancer mortality, while cervical cancer deaths tended to occur in younger age-groups 2 , 36 (up to 5.5% annually). 5 …”
Section: Discussionmentioning
confidence: 99%
“… 1 China contributes to more than 18% of the global cervical cancer burden, with 106,000 cases and 48,000 deaths. 1 Human suffering, societal burden, and high economic costs associated with cancer have been reported in many countries 2 , 3 , 4 , including China. 2 Although the maximum incidence rate is recorded around the age of 40 years, the number of cervical cancer cases is increasing at an alarming rate among younger women in China, 5 that is, approximately 11 cases per 100,000, with an annual increase of 3.05% ( P ​< ​0.001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among women with invasive CC, around 70% are diagnosed with locally advanced disease. These figures speak on deficiencies in coverage and timely diagnosis and treatment of detected preinvasive and invasive lesions (2)(3)(4).…”
Section: Cervical Cancer In Mexicomentioning
confidence: 99%
“…1,2 There are about 500,000 new cases of cervical cancer every year in the world, 85% of which are in developing countries, and about 250,000 people die of cervical cancer each year. 3,4 In China, 140,000 new cases are discovered every year, accounting for about one third of the global patients with cervical cancer, and about 50,000 patients die of cervical cancer every year. 5,6 In recent years, the incidence of cervical cancer has a younger trend.…”
Section: Introductionmentioning
confidence: 99%